Activities of the summer party of the 28th Japanese Antarctic Research Expedition in 1986-1987 - Takao Hoshiai (National Institute of Polar Research, 1989)
The summer operations of the 28th Japanese Antarctic Research Expedition (JARE-28) in 1986-1987 are described. The icebreaker SHIRASE, carrying 52 expedition members led by the present author, 4 Japanese observers with cargos of about 900t, left Tokyo on 14 November 1986. After calling at Fremantle, Western Australia, where 2 Belgian scientists participated in, the ship arrived at Breid Bay on 17 December. With helicopters unloading of 300t cargos was completed by 5 January 1987. Surface transportation of cargos to and construction of buildings at Asuka Station were concurrently carried out. An aerial photographic survey was also done in the Sor Rondane Mountains region. After departure of the SHIRASE for Syowa Station on 5 January, the construction was continued and the field work of geosciences in the Sor Rondane Mountains region was commenced. The ship reached Syowa Station on 9 January. Relief operations and field research work were completed by the end of January. The SHIRASE left Syowa on 4 February and arrived again at Breid Bay on 6 February. Summer personnel of JARE-28 who completed construction at Asuka and field work in the central part of the Sφr Rondane Mountains region and also the members of inland traverse party of JARE-27 were picked up there by 14 February. Then the ship left on 15 February and returned to Tokyo on 20 April via Port Louis, Mauritius and Singapore. The following researches were carried out during the summer operation of JARE-28 : a) aerial photographic survey, geological, geomorphological and geodetic observations in the Sor Rondane Mountains region; b) terrestrial biological and oceanographical observations and gravity measurement in the Syowa Station area; c) ionospheric, meteorological and oceanographical observations and sea gravity measurement on board the SHIRASE.